Peningkatan Aktivitas dan Hasil Belajar Siswa pada Mata Pelajaran Biologi Melalui Model Pembelajaran Make and Match Berbasis Media Karu Pintar - Ainur Rosidha (Jurnal Paedagogy, 2020)
This study aims to improve student activity and learning outcomes in biology subjects through the "Make and Match" learning model with Smart Card media. This research method uses classroom action research. This research was conducted on 21 students of class X-ATU-1 SMK Muhammadiyah 1 Batu. The research instrument used tests, interviews, and observations. The data analysis technique used qualitative and quantitative descriptive analysis. The results of this study indicate an increase in activity and student learning outcomes in the post test cycle I and post test cycle II. It can be seen from the observation that student activity has increased in each cycle, namely 73% in cycle I and increased again to 93% in cycle 2, students become more active in participating in learning with smart card-based make and match models and complete student learning outcomes. and student learning outcomes also experienced an increase in each cycle, namely 62.5% of students completed with an average score of 68.5 in the post-test cycle I, and increased again to 82% of students completed with an average score of 83 in the post-test cycle II.